Modeling plastic anisotropy evolution of AISI 304 steel sheets by a polynomial yield function - Sener, Bora; Esener, Emre; Firat, Mehmet (SPRINGER INT PUBL AG, 2021)
In this study, a numerical model for the evolution of plastic anisotropy is investigated for the purpose of stamping method design by Finite Element (FE) analysis and proved experimentally via process simulations of a cold-rolled austenitic stainless steel (AISI 304) sheet. The plastic anisotropy of the sheets is described with a fourth-order homogenous polynomial yield function and this modelling approach is enhanced by plastic strain dependent material coefficients. Tensile tests of coupon specimens taken along the different directions from rolling direction, and flow strength and deformation anisotropies are described with the planar variations of yield stress and plastic strain ratio computed at four plastic strain levels (0.002, 0.02, 0.05 and 0.18). A new numerical approach is, then, applied to identify polynomial coefficients ensuring an orthotropic positive-definite, convex yield surface with a well-defined stress gradient at every loading point on plane stress subspace. The developed computational model is implemented into general purpose explicit FE analysis software Ls-Dyna by a user-defined material model subroutine (UMAT) and applied in the stamping simulation of AISI 304 steel rectangular cups for the house-hold applications. The computed thickness distributions and the flange geometries were compared with measurements and it was observed that the best predictions were done with material parameters at %5 plastic strain level.
Keywords: Stamping; Anisotropy evolution; Polynomial yield criterion; AISI 304 stainless steel; ALUMINUM-ALLOY SHEETS; STRAIN RATIO; CRITERION; FLOW; TENSION; METAL; Science & Technology - Other Topics